Correlation Between Quantitative Hepatitis B Surface Antigen and Hepatitis B Virus Deoxyribonucleic Acid Levels in Hepatitis B e Antigen-Positive and Hepatitis B e AntigenNegative Chronic Hepatitis B Patients - Nirmala, Viva Finhar Insani; Aryati, A.; Susianti, Hani; Mustika, Syifa (Turkish Journal of Gastroenterology, 2020)
Background: This study aimed to analyze the relationship between quantitative hepatitis B surface antigen and hepatitis B virus deoxyribonucleic acid in hepatitis B e antigen-positive and hepatitis B e antigen-negative chronic hepatitis B patients and to determine the best cut-off value for quantitative hepatitis B surface antigen to predict high hepatitis B virus deoxyribonucleic acid levels (≥2000 IU/mL).Methods: Ninety-seven sera from chronic hepatitis B patients were collected in this study. Hepatitis B virus deoxyribonucleic acid levels were quantified by real-time polymerase chain reaction. Quantitative hepatitis B surface antigen and hepatitis B e antigen levels were determined by two-site sandwich chemiluminescence immunoassay. Alanine transaminase levels were measured by the International Federation of Clinical Chemistry-approved methods.Results: A significant correlation between quantitative hepatitis B surface antigen and hepatitis B virus deoxyribonucleic acid levels was observed in hepatitis B e antigen-positive group (r = 0.453, P = .002), but not in hepatitis B e antigen-negative group (r = 0.117, P = .454). No significant correlation between quantitative hepatitis B surface antigen and alanine transaminase was found in the hepatitis B e antigen-positive group (r = 0.521, P = .241). However, a significant correlation was shown between quantitative hepatitis B surface antigen and alanine transaminase levels in the hepatitis B e antigen-negative group (r = 0.455, P = .001). The best cut-off value of quantitative hepatitis B surface antigen for predicting high hepatitis B virus deoxyribonucleic acid levels was 3.422 × 103 IU/mL.Conclusion: Correlation between quantitative hepatitis B surface antigen and hepatitis B virus deoxyribonucleic acid levels is significant in the hepatitis B e antigen-positive group. Quantitative hepatitis B surface antigen can be used to predict high hepatitis B virus deoxyribonucleic acid levels in the hepatitis B e antigen-positive groupCite this article as: Nirmala VFI, Aryati A, Susianti H, Mustika S. Correlation between quantitative hepatitis B surface antigen and hepatitis B virus deoxyribonucleic acid levels in hepatitis B e antigen-positive and hepatitis B e antigen-negative chronic hepatitis B patients. Turk J Gastroenterol. 2023;34(4):378-382.